2016
DOI: 10.1097/meg.0000000000000628
|View full text |Cite
|
Sign up to set email alerts
|

Short article: Negative small-bowel cross-sectional imaging does not exclude capsule retention in high-risk patients

Abstract: The capsule retention rate is similar in low-risk and negative PC high-risk patients. Conversely, high-risk patients with negative SBCSI have a significantly higher capsule retention rate. Our data suggest that in high-risk patients, negative SBCSI examination is not reassuring and, when SBCE is indicated, PC should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…For predicting CE retention, two methods have been attempted: dedicated small bowel cross-sectional techniques; and patency capsules. However, cross-sectional techniques and patency capsules are both effective in decreasing the retention rate, although neither able to completely eliminate the risk for retention [24]. We found that passage of the capsule was delayed in 10% of CD patients and 12.5% of intestinal tuberculosis patients.…”
mentioning
confidence: 69%
“…For predicting CE retention, two methods have been attempted: dedicated small bowel cross-sectional techniques; and patency capsules. However, cross-sectional techniques and patency capsules are both effective in decreasing the retention rate, although neither able to completely eliminate the risk for retention [24]. We found that passage of the capsule was delayed in 10% of CD patients and 12.5% of intestinal tuberculosis patients.…”
mentioning
confidence: 69%
“…In the constrained by human error. 14 Some works suggest that physicians' performance is disappointing 15,16 and that the reporting accuracy in SBCE declines after reading a single capsule study. 17 Because incomplete visualization of the SB in terms of coverage and/or image quality affects mainly the detection and reporting of neoplastic lesions, 18 it becomes evident that adjustable frame rate and higher-resolution images are needed.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, it still has several significant limitations such as the use, type, and timing of bowel preparation 20 ; the time required for conventional SBCE reading; and the overall suboptimal interobserver agreement between readers. 16 Moreover, the clinical relevance of any findings is vital for a conclusive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The main relevant limitation of VCE is the long time needed to review the recordings. The evaluation of small bowel mucosa is performed by an expert endoscopist who dedicates a slot of one working day for reading the entire VCE recording, with relevant costs [12]. Therefore, a pre-reading procedure performed by an expert and a specifically trained nurse would result in a time reduction of successive medical evaluations, as long as the initial assessment was accurate.…”
Section: Discussionmentioning
confidence: 99%